NATIONAL HANATIONAL HANDICRAFTS: TRADITIONS EVOLVED FROM DOMESTIC PRACTICE TO CULTURAL REPRESENTATIONNDICRAFTS: TRADITIONS EVOLVED FROM DOMESTIC PRACTICE TO CULTURAL REPRESENTATION (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
National handicrafts are more than decorative artifacts or commercial products—they are embodiments of cultural memory, intergenerational knowledge, and lived experience. In Uzbekistan, traditional crafts such as embroidery, pottery, wood carving, textile weaving, and metalwork have long shaped the rhythm and aesthetics of daily life. Historically rooted in necessity and spiritual symbolism, these crafts have served both utilitarian and expressive functions—enriching homes, rituals, and communities through beauty and meaning.This article examines the evolution of Uzbek national handicrafts from functional household practices to celebrated cultural expressions showcased on global platforms. It explores how once-private artisanal knowledge—primarily preserved through domestic labor and family lineages—has been elevated to the status of cultural heritage through institutional support, state recognition, and global interest in intangible traditions. Drawing on field research, artisan interviews, and policy analysis, the study investigates the factors driving the revival of traditional crafts in Uzbekistan. These include post-independence nation-building efforts, tourism development, women's economic empowerment, and a global shift toward sustainability and slow production. The article highlights the role of artisans not only as producers but as cultural ambassadors—translating the visual language of their ancestors into contemporary art, design, and identity. The transformation of national handicrafts into symbols of cultural identity is also analyzed within the context of globalization. In the 21st century, Uzbek crafts are exhibited at international expos, integrated into high fashion collections, and promoted as tools of soft power. While commercialization brings new opportunities, it also raises challenges related to authenticity, cultural appropriation, and the preservation of craftsmanship standards. Ultimately, this article argues that the movement of handicrafts from the private sphere of everyday life to the public stage of cultural diplomacy reflects more than a change in function—it signifies the resilience, adaptability, and continued relevance of traditional arts in shaping national consciousness. In the hands of today’s artisans, these crafts are not relics of the past, but evolving narratives that connect tradition with innovation, and heritage with global identity.